If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -11 = 21 Reorder the terms: -11 + 3y = 21 Solving -11 + 3y = 21 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 3y = 21 + 11 Combine like terms: -11 + 11 = 0 0 + 3y = 21 + 11 3y = 21 + 11 Combine like terms: 21 + 11 = 32 3y = 32 Divide each side by '3'. y = 10.66666667 Simplifying y = 10.66666667
| 3x+m=16 | | -2.8/7 | | factorisemn=m | | 3(2x-1)=x+27 | | 15-4(2a-1)= | | 3(x-4)=24 | | 4cosx+1=0 | | y=9x^3-7x+2 | | 4c-1=-5 | | 12t=howmenylb | | X+7.1=4.1 | | 3p^2-6p=1 | | 187=88-y | | 1+(4*4)-2= | | S+4.1=8.1 | | 1*10= | | n^2/3-n/6 | | 52x+3=1 | | (3/4)n | | y^2/2=32 | | 9a-8+6a-4= | | 2(3-8)+7= | | y=-5+4sinx | | (5)+(-14)= | | f(x)=-0.91666667*x+1.5 | | (11)+(-3)= | | 6/5cos-1(y/8)=pi | | 16x^6-10x^4/2x^3 | | x-(5x+2)=-4(x-3) | | (-9)+-(14)= | | -x/2*x | | (15)+(-10)= |